Pembuatan kompos dari pupuk kandang dan serbuk kayu di Green House Universitas Sulawesi Barat sebagai sarana pemberian ilmu bagi mahasiswa - Lica, Angel; Greis, Greis; Alibas, Sitti Fadlia; Permadi, Aisyah; Annisa, Fatimah; Putri, Siti Nurzulbaeni Yanti; Afila, Amanda; Zakinah, Nurul; Nurliana, Nurliana; Budi, Ikhsan; Malik, Abdul; Saputra, Satrio Sahban; Muhaimin, Muhaimin; Rudi, Rudi (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
Excessive use of inorganic fertilizers can cause soil degradation and environmental pollution. To address this issue, composting organic materials such as manure and wood chips can be an environmentally friendly alternative solution. This program aimed to demonstrate the composting process for a mixture of manure and wood chips through activities conducted by students of the Agroecotechnology Study Program at Universitas Sulawesi Barat, class of 2022, in the greenhouse. Compost was made by mixing 20 buckets of wood powder with 20 kg of manure, adding 35 ml of EM4 solution dissolved in 1 liter of water, and fermenting for 2-3 weeks. The results of the practical activity showed that the compost produced was dark brown, had an earthy smell, and had a crumbly texture, indicating that the decomposition process was successful. This compost has the potential to increase soil fertility, improve soil structure, and support sustainable agriculture in an efficient and environmentally friendly manner.